Análise das alterações na temperatura cutânea durante o ciclo menstrual - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Introduction: The menstrual cycle is responsible for several changes in the female biological cycle, among them the concentrations of follicle stimulating hormones, luteinizing, estrogen and progesterone. Changes in estrogen and progesterone levels are capable of interfering with body thermoregulation. The infrared thermography is a method capable of identifying physiological changes which reflect over the human body cutaneous temperature, being used as a diagnosis and analyzis method for several conditions. However, the studies found do not mention the hypothesis of menstrual cycle interfering in thermographic results. Objective: to check for changes on skin temperature during the menstrual cycle. Materials and Methods: This is a descriptive study, experimental, with a quantitative approach, in which the convenience sample consisted of 15 healthy women, aged between 18 and 41 years (± 24.3 years). These were evaluated using infrared thermography and bioimpedance in the follicular, ovulatory and luteal phases of the menstrual cycle. Results: Regarding skin temperature, there were only significant differences between the 3 phases on the abdominal temperature (p = 0.034) and the lumbar region (p = 0.047). On the abdomen, the differences were close to the statistical significance between the follicular and luteal phases (p = 0.053) and significant between the ovulatory and luteal phases (p = 0.020), that is, the temperature did not change between the folicular (M = 30.91 ) and ovulatory phases (30.85), and decreased significantly in the luteal phase (30.33), while on the lumbar region, there were only significant differences between the ovulatory and luteal phases (p = 0.004), with a reduction in the average temperature from 31.98 to 31.56. Regarding the analysis of body composition, there were no significant differences in the total and segmented body water between the 3 evaluations. Conclusion: there was a significant change on the cutaneous temperature of the abdominal and lumbar region between the ovulatory and luteal phases of the menstrual cycle
Keywords: Ciclo menstrual - Aspectos fisiológicos; Menstruação; Mulheres - Saúde e higiene; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CNPQ::CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::GINECOLOGIA E OBSTETRICIA